How Do Local Governments Interpret International Norms on Sustainable Development in Circular Economy Practices? - Baharuddin, Aswin; Muntazar, Muhammad Firdaus Al; Fadzila, Fara Fahira Dwi; Rahmatia, Rahmatia; Hidayat, Muhammad Fikri; Lubis, Adelita; Lubis, Mia Aulina (Glocal Society Journal, 2024)
As a program that can support a healthy economy, CE has an essential role in changing the face of cities. CE is considered to have a close relationship with the SDGs, SDG 12 Responsible Consumption and Production. The application of CE in different cities also allows the emergence of various policy models, each of which seeks to answer the city's unique challenges. This research seeks to map the state-of-the-art of CE, SDG 12, and cities. The research method used for the mapping is a systematic literature review using Mendeley's website as a database. This research finds that CE and SDGs are correlated through the norms of sustainable development but that the relationship between CE and sustainable development is itself a tool-and-target relationship. In addition, through best practices from 6 cities that have implemented CE, three types of determinants can be identified that can drive the transition to CE, multi-actor symbiosis, restoration and preservation of public spaces, and internalization of CE cultural values. Makassar City has much potential through Sustainable Development-based policies such as "Five Star TPA" and "Lorong Garden".